Public Responsiveness to Declining Crime Rates in the United States and England and Wales - Enns, Peter K. (The British journal of criminology, 2022)
During much of the second half of the twentieth century, public opinion in both the United States and Britain became more punitive as crime rates rose. These shifting public attitudes had a profound influence on criminal justice policies. What is less understood is how public attitudes in these countries have responded to declining crime rates since the early-1990s. To understand how the public reacts to declining crime rates, we focus on crimes recorded by the police as well as data on actual victimisation. We also draw on more than 4,000 national survey questions to construct measures of public concern about crime and support for punitive criminal justice responses. Our analyses illustrate parallels in the crime drop measured by victimisation surveys in the two countries (with recorded violent crime in England and Wales the exception to this overall trend). The over-time patterns in public concern about crime and punitive sentiment are more complex, with the US public becoming less punitive (in line with declining crime rates) while the British public’s concern with crime appears more in tune with actual crime rates. Given the distinct social, political and institutional settings offered by the two countries, the parallel dynamics of crime and the mixed response of public opinion help illustrate the importance of the comparative analysis of crime and its effects on society as well as the importance of considering multiple measures of public opinion related to crime and punishment.